(untitled) (World of finance, 2019)
Introduction. Today in the conditions of European integration in Ukraine, the development of industries with a great innovative potential is becoming urgent, which is impossible without attracting funding. Therefore, the methodological toolkit for financing innovation in the field of agribusiness should provide competitive advantages for Ukrainian producers and stimulate economic growth. Purpose. The article is devoted to the study of methodical tools for attracting financial resources into the innovative activities of enterprises of the agro-industrial complex. Results. According to the statistics, it is determined that the main source of financing for innovation activity in Ukraine is the enterprise’s own resources, and the most promising sector for attracting investments in Ukraine is the agro industry. The modern methods of financing innovative activity in the agro-industrial complex are explored in the article. Based on a comparative analysis, the potential benefits and risks of applying the methods of financing the innovation activity of enterprises are determined. The criteria for innovation and investment attractiveness of enterprises that attract financial resources for innovation are proposed. Conclusions. The agro-industrial complex is a priority investment direction for domestic and foreign investors. The scientific approach to the application of financing methods in innovation is required now. In modern conditions various methods of financing the innovation activity of the agro-industrial complex have been formed, among which special attention should be paid to financing through venture capital, the involvement of business angels and the development of state funding and support programs for agribusiness. The optimal way of attracting resources into the agribusiness is to create an optimal structure of financing from different sources. For those who plan to finance innovative activities in the agroindustrial complex, it is advisable to use the relevant criteria of the investment and innovation attractiveness of the enterprise in order to identify the most promising and reliable enterprises.